Effect of aerosol and oral fenoterol on histamine and methacholine challenge in asthmatic subjects. - Salome, C M (1981)
In order to determine the effect of drugs on bronchial hyperreactivity in subjects with asthma, 12 atopic asthmatic volunteers underwent bronchial challenge with either histamine or methacholine on three separate days. Before the challenges no medication was given on the first day, on the second 400 microgram of aerosol fenoterol and on the third 5 mg of oral fenoterol were administered. The aerosol fenoterol caused the dose response curves to both histamine and methacholine to be shifted to the right in all subjects. The oral dose produced no significant change from the control values. The slope of the dose response curves was not altered by either the oral or the aerosol drug. It is concluded that aerosol but not oral fenoterol in the clinical dosage, causes a change in the sensitivity but not in the reactivity of the airway of patients with atopic asthma.